The predicative value of early quantitative electroencephalograph in epilepsy after severe traumatic brain injury in children - Bai, Wei (Frontiers in Pediatrics, 2024)
Objective: To explore whether early quantitative electroencephalograph (EEG) can predict the development of epilepsy in pediatric patients with severe traumatic brain injury (TBI). Methods: A total of 78 children with severe TBI who were admitted to our hospital were divided into post-traumatic epilepsy (PTE) and non-PTE groups according to whether or not they developed PTE. EEGs of frontal, central and parietal lobes were recorded at the time of their admission. The power values of each frequency band, odds ratio and peak envelope power values of each brain region were statistically analyzed. In addition, the patients were followed up for two years, and the occurrence of PTE was documented. Results: During the follow-up period, PTE occurred in 8 patients. Analysis of EEG signals across different brain regions (frontal, central, and parietal lobes) revealed significant differences between the PTE and non-PTE groups. Patients with PTE exhibited significantly higher δ and θ power values (P < 0.01), lower α/θ ratios (P < 0.01), and elevated θ/β, (δ + θ)/(α + β), and peak envelope power (P < 0.01) compared to those in the non-PTE group. Conclusion: In children with severe TBI, the parameter characterization of early quantitative EEG has potential application in predicting PTE.